2017
DOI: 10.2215/cjn.10871016
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Demographic Trends in Glomerular Disease Epidemiology in the Southeastern United States, 1986–2015

Abstract: We identified significant changes in relative renal biopsy frequencies of many glomerular disease subtypes over three decades. Temporal trends were consistently observed within all major demographic groups, although relative predominance of individual glomerular disease subtypes differed according to patient age, sex, and race. We propose that exploration of behavioral and environmental exposures that likely underlie these findings should be the focus of future hypothesis-driven research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
111
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 23 publications
8
111
10
Order By: Relevance
“…IgAN and FSGS, although IgAN is still the most common PGN. A similar finding was also observed in other Chinese subpopulations [17], while the frequency of IgAN has remained stable in the USA [23]. The decline in FSGS frequency has been previously observed in the Chinese population [17].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…IgAN and FSGS, although IgAN is still the most common PGN. A similar finding was also observed in other Chinese subpopulations [17], while the frequency of IgAN has remained stable in the USA [23]. The decline in FSGS frequency has been previously observed in the Chinese population [17].…”
Section: Discussionsupporting
confidence: 87%
“…The decline in FSGS frequency has been previously observed in the Chinese population [17]. Previous studies from the USA showed an increase in the frequency of FSGS, which was followed by a plateau and decline in its frequency in the 21st century [23].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Epidemiology, Demographics, and Genetics MPA, GPA, and EGPA have a peak incidence of 65-75, but may occur at any age, with a slight male predominance (12). Figure 3 shows data derived from 21,374 patients with any form of glomerular disease identified in renal biopsy specimens evaluated by the University of North Carolina Nephropathology Laboratory from 1986 to 2015 (13). Only a subset of the most common glomerular disease categories that cause GN are shown on these graphs.…”
Section: Serologic Classificationmentioning
confidence: 99%
“…Only a subset of the most common glomerular disease categories that cause GN are shown on these graphs. In patients with GN ,60 years old, lupus nephritis and IgA nephropathy are diagnosed most often, whereas ANCA GN is diagnosed most often after 60 years old (13). As a percentage of all biopsies performed in different age groups (panel on the right in Figure 3), IgA nephropathy declines with age, lupus nephritis peaks in early adulthood, and ANCA GN increases with age, with a dramatic surge after 50 years old.…”
Section: Serologic Classificationmentioning
confidence: 99%